Conch strombus as indicator of metal contaminations in Southern and Eastern Johor waters - Sabri, Shaikhah (2015)
Water quality of the Johor coastal areas especially from Straits of Johor has long shown high level of metals. Conch Strombus which colonize near the shore ecosystem is exposed to metals in the aquatic environment. This study was carried out to evaluate the use of Strombus as an indicator of metals contamination at Johor coastal area. Moreover, Strombus is also a popular food source with high commercial value in the southern part of Peninsular Malaysia. Therefore, assessment on the metal status is crucial since direct consumption of contaminated seafood would cause adverse effect to human health. Strombus’s specimens, sediment and seawater samples were collected during spring low tide from July 2010 to July 2012 at seven different sites. There were three species of Strombus found during this study i.e Strombus canarium, Strombus urceus and Strombus aratrum. Strombus canarium turned to be the most abundance and highly distributed compared to other species. The metal concentrations (As, Cd, Cu, Pb and Zn) in the sediment, seawater and soft tissues of S. canarium were analyzed using inductively coupled plasma mass spectroscopy (ICP-MS). All of the metal concentration except for As exceeded the permissible limit of Malaysia Marine Water Quality Criteria (MMWQC) for Class E where Zn shows the highest range in water (0.002-0.165 mg/L) as well as in sediment (23.903-56.286 µg/g dry weight). Overall, high concentrations of metals were recorded at western part of Johor Straits. Metal content in sediment could be classified as polluted with Cu (7.247-46.868 µg/g dry weight) according to the Environmental Protection Agency (EPA) sediment quality. S. canarium also contained high accumulation of Zn (13.270-22.082 mg/kg wet weight). Nevertheless, all metal concentration in the soft tissues of S. canarium was within the recommended limit of Food and Agriculture Organization (FAO) and World Health Organization (WHO). On the other hand, experiments on toxicity were also carried out and reported as median lethal concentration (LC50). Abnormal behavior such as secretion of mucus in large quantities was observed, especially at high concentration of metals. Cu appeared to be more toxic than other metals with the value of LC50, 0.261 mg/L. Generally, the result indicates that the S. canarium can be employed as bio-indicator for metal contamination since they tend to reflect the quality of surrounding environment.